Otimização de elementos pré- moldados de concreto: lajes alveolares e vigas com cabo reto - Vasconcelos, Rebeca Freitas (2014)
This work presents the application of optimization techniques for the design of hollow core slabs and beams with precast and prestressed straight cable, considering the calculation of both the immediate losses as the time-dependent. For the slabs formulation allows the designer to obtain the optimal dimensions of the height of the panel, the diameters of the cables and the alveoli, and the number of cables. The beams are obtained beam height, diameter and the number of cables. Are still subject to the conditions of service for bending stresses, constructive limitations and failure conditions. Illustrative examples are presented using the Branch and Bound algorithm and Lingo (PLS), further comparison is made between the weight and the cost of the panel, and from the results of the algorithm and sizing Munte tables that follow Brazilian standards. We conclude that the optimal design has many advantages compared to conventional design, methods of discrete variation that best characterize the optimal variables of the problem, restrictions on the normal stresses ELS are crucial in obtaining the optimal dimensions of the structures and lower panels weight does not necessarily represent the lowest cost.